1999
DOI: 10.1093/humrep/14.11.2727
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial CD56+ natural killer cells in women with recurrent miscarriage: a histomorphometric study

Abstract: Endometrial natural killer (NK) cells were compared in luteal-phase endometrial samples from women with recurrent miscarriage and from normal subjects. Cryostat sections were labelled using a monoclonal antibody to CD56 using an avidin-biotin complex method and a morphometric study performed. Increased mean numbers of CD56+ cells were documented in the endometrium of women with recurrent early miscarriage only. These findings suggest a possible role for NK cells in the pathogenesis of recurrent early pregnancy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
111
1
4

Year Published

2001
2001
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(121 citation statements)
references
References 28 publications
5
111
1
4
Order By: Relevance
“…Furthermore, numbers of uNK cells have been reported to be altered in pre-eclampsia (Williams et al 2009), although results are inconsistent, and several groups have reported increased uNK cells in mid-secretoryphase endometrium from women with a history of recurrent miscarriage or recurrent implantation failure (Clifford et al 1999, Laird et al 2003, Quenby & Farquharson 2006. As the uNK cells are the predominant decidual leukocyte population in early pregnancy, many roles have been suggested for them.…”
Section: Decidual/uterine Nk Cellsmentioning
confidence: 99%
“…Furthermore, numbers of uNK cells have been reported to be altered in pre-eclampsia (Williams et al 2009), although results are inconsistent, and several groups have reported increased uNK cells in mid-secretoryphase endometrium from women with a history of recurrent miscarriage or recurrent implantation failure (Clifford et al 1999, Laird et al 2003, Quenby & Farquharson 2006. As the uNK cells are the predominant decidual leukocyte population in early pregnancy, many roles have been suggested for them.…”
Section: Decidual/uterine Nk Cellsmentioning
confidence: 99%
“…For example, increased numbers of CD56+ NK cells have been reported in decidua of women with sporadic miscarriage compared with controls (Zenclussen et al, 2001), although we were not able to confirm this finding in a study of placental bed biopsies from aneuploid and euploid miscarriages from 8 -20 weeks gestation, compared with normal pregnancy (Scaife et al, 2004). Despite the inconsistency of data for decidual and peripheral blood leukocytes, there are several independent reports from different groups of increased numbers of uNK cells, detected using immunohistochemistry, in luteal phase endometrium of both women with unexplained recurrent miscarriage and recurrent implantation failure (Quenby et al, 1999;Clifford et al, 1999;Laird et al, 2005;Tuckerman et al, 2007). Furthermore, it has been suggested that high uNK cell numbers in mid-secretory phase endometrium from women with recurrent miscarriage predicted miscarriage in subsequent pregnancy (Quenby et al, 1999).…”
Section: Uterine Nk Cells In Pathological Pregnancymentioning
confidence: 99%
“…CD56 + CD16 + uNK cells were found in 85% [68/80] of the studied decidua specimens of women with unexplained repeated miscarriage. Quenby et al (16) reported that women with RM had significantly more uNK than controls, and Clifford et al (37) also showed increased CD56+ uK cells in women with unexplained repeated miscarriage. Increased expression of CD56 + CD16 + uNK was also reported in deciduas obtained after spontaneous miscarriage in women with a history of repeated miscarriage (38 Women refused to participate in the study and the use of tissue culture and conventional G-banding for cytogenic analysis and karyotyping of abortion specimens were limitations during this study.…”
Section: Discussionmentioning
confidence: 99%